“Não há ritual sem falhas”: lamentações, denúncias e resistência - relação matrimonial no discurso de mulheres evangélicas - Pontes, Leila Silvana (2023)
The present research, supported by theoretical and methodological studies of the French Discourse Analysis coined by the philosopher Michel Pêcheux, analyzes the discourse of evangelical women about family and marriage relationships. The corpus of the work consists of clippings of sermons by Pastor Helena Tannure (videos) broadcast on Youtube and testimonial referring to these sermons, enunciated by evangelical women who have difficulties in their relationships. Regarding the selection of the corpus, the criterion for choosing the sermons was due to the interest of the analyst in the themes and, about the testimonies, the criterion was the fact that the women approached about their family and marriage relationship and comments about your companions. The study departs from the postulate of Pêcheux (2014, p. 281) that “there is no domination without resistance” and, therefore, defends the thesis that the women of the corpus, even permeated by a religious ideology of patriarchal basis, which imposes them submission to man, establishing a hierarchical relationship, in which they are considered inferior to them, in addition to limiting them to the private space. They contradict and confront the dominant ideology and make their voice heard, a voice of insubmission, therefore of resistance. In view of this, the central objective of the research is to observe, in the corpus, where the ritual fails, in order to deconstruct the evidence produced by the dominant ideology that the woman, in the singular framework delimited for this study, is genuinely passive and conformed to the submission status. The main objective directs the analysis towards specific objectives, considering that understand discursively how these resistance works of these women and how the resistance results in rupture, a fact that directed the research to language lapses, discursive memory and denial present in the corpus. From this, It was sought to understand how these women signify their subject position within family and marriage relationships and how men are discoursed. To help this study, along with concepts of Discourse analysis, the corpus led to trigger knowledge about some religious terms and also about Psychoanalysis concepts. Thus, the term 'evangelical' and the concept of Language Lapses/ Failure were highlighted; of Discursive Memory and Negation. Among the main names that support this research are: Pêcheux (1999, 2014, 2015), Freud (2014, 1966 [1901]), Orlandi (2015, 2017), Cunha (2007), Lerner (2019), Muraro (1995), e Anderson (2019)